P28 Introduction of an intravenous (IV) medications skills course for foundation year 1 (FY1) doctors). (5th November 2017) - Bailey, PF; Woodier, N; Love, C; Fores, MA
Abstract : Introduction: There is limited time for training in the preparation and administration of medications in undergraduate medical education. Medication safety is a key component of patient safety. Locally, medication related incidents were the most common by report (NUH DATIX, 2016) and research has shown that FY1 doctors feel that their knowledge of clinical pharmacology is poor with undergraduate teaching that did not equip them for clinical practice (Tobaiqy et al., 2007). The aim of the course was to improve medication safety through practice of IV drug administration for FY1 doctors at NUH. Methods: The course was co-designed by representatives of Trent Simulation and Clinical Skills Centre (TSCSC) and the Trust's Pharmacy Department with a multiprofessional faculty also involving colleagues from the Nursing Practice Development Team. A total of 98 FY1 Doctors attended the course involving rotation through 4 simulated practical skill stations relating to the administration of IV medications. A pre and post course questionnaire was completed, followed by a questionnaire sent to candidates 6 weeks post course in order to identify any learning outcomes translated into clinical practice. Results: The pre-course data identified that 56% of participants felt competent in medication prescription whilst only 26% felt competent in administering medications by all routes. Post course data identified that candidates felt the course provided them with useful new skills (93%), knowledge (95%), was delivered at an appropriate level (97%). The 6  week post course survey (31% response rate) demonstrated 100% would recommend a medications skills course and of those who responded 78% also felt the course helped make them a safer practitioner. Discussion: Our data corroborates the perceived gap between current education and self-perceived competence to perform the skills associated with preparing and administering medications amongst FY1 doctors. Attending a co-designed simulation-based course with multiprofessional faculty enabled candidates to improve the requisite gaps in knowledge and skills in order to help improve practice and benefit patient safety. Recommendation: Candidates felt the course was effective, providing useful skills/knowledge and was positively evaluated, which supports the case for offering this training to subsequent FY1 cohorts. Future developments would be to track candidates into practice more effectively to establish that learning is observed or shown to be translated into practice. Equally if we identify issues with this translation it might enable future programmes to be better designed. References: . NUH DATIX. Nottingham University Hospitals (NUH) NHS Trust. DATIX incident reporting system 2016. . Tobaiqy M, et al. Foundation year 1 doctors and clinical pharmacology and therapeutics teaching: A retrospective view in light of experience. Br J Clin Pharmacol 2007;64:363–72.